INTERIOR LANDSCAPE;THE LANDSCAPE ON BOTH SIDES OF THE CAMERA reflections on art, creativity, expression, and a life in photography. - Tal, Guy (ROCKY NOOK, 2022)
A deeply thoughtful and inspiring collection of essays about visual expression, art, creativity, and a life in photography Photographer, teacher, and author Guy Tal has been photographing the landscape for more than 30 years, and in that time he has also been consistently contributing to the literature of photography, writing not about the technical aspects of the photograph--the gear, the exposure details, the "secrets to getting a great shot"--but about the deeper topics of visual expression, creativity, art, and life. Building on the legacy of his previous best-selling books More Than a Rock and Another Day Not Wasted, as well as his work as a regular contributor to LensWork and On Landscape magazines, The Interior Landscape is a collection of more than 60 brief essays, packaged in a beautiful hardcover format and illustrated throughout with Guy's stunning photography. Organized into four parts, Guy discusses: • Creativity and expression as the most significant aspects of making art • The controversial and tenuous relationship between photography (by design a medium for objective representation) and art (by definition the subjective expressions of the imagination of artists) • How he has formed a relationship with, and found meaning in, the natural landscape, and how he expresses these meanings in his photographs • Lessons learned from more than three decades of practicing expressive landscape photography The Interior Landscape is for anyone interested in, as the title suggests, turning inward to explore creativity, art, expression, and the landscape. It is sure to illuminate, educate, and inspire you on your photographic journey.